Meningkatkan Keterampilan Membaca melalui Media Big Book pada Siswa Kelas IA MI Nurul Islam Kalibendo Pasirian Lumajang - Moch. Mahsun; Miftakul Koiriyah (Bidayatuna, 2019)
For low-level students the reading stage is to read the beginning. Pre-reading to low-grade students is the foundation of the speed-reading, extensive reading, and reading comprehension stages that are indispensable in high-level classes. So that the teacher must really hone students' beginning reading skills. The teacher has not fully utilized the media in learning to read. The position of the teaching media is in the teaching method component as an effort to enhance the process of teacher-student interaction and student interaction with their learning environment. One of the supports for learning to start reading is teaching reading skills such as letter cards, picture series, big books, story calendars, and picture story books. These media are very easy to obtain or make by the teacher himself. The focus of this research is to improve learning early reading skills through the big book media for class IA MI Nurul Islam Kalibendo, Pasirian District, Lumajang Regency. Based on the results of the research and discussion that has been done, it can be concluded that the learning of early reading skills leads to a significant increase based on the activeness and enthusiasm of students during learning. So that this can be increased by using the big book media maximally. This is evidenced by the average value of students' initial reading skills after the action increased to 93.3%.